Topical issues of source studies of the history of Kazakh music - Мылтыкбаева, М.; Мосиенко, Дина; Абдинуров, А. (Pedagogy and Psychology, 2022)
This article is devoted to the study of the current state of source studies in Russian musicology: now researchers face new challenges due to factors such as globalization, openness of cultural borders, and, at the same time, spiritual revival and self-determination of the nation. The issues of source studies as a scientific and academic discipline aimed at creating a full–fledged source study - a complex process that includes both source analysis and art synthesis - are becoming relevant. The value of source studies and the illumination of the problems of musical source studies in the works of domestic and foreign scientists are noted, determine the importance of source studies for musicology, which provide historical research with objectivity and accuracy of scientific conclusions, directs the researcher's attention to the study of the maximum number of sources, and also builds a system of such scientific research. In the work on the study, cultural-historical, comparative methods were used. Based on the analysis of scientific literature on the history of Kazakh music, the main problems that have developed in one of the most important areas of applied musicology are revealed. There is a low level of development of source studies in Russian science, an acute shortage of various kinds of source studies, the absence of works that specifically consider the specifics of working with musical monuments and documents of the past. Certain achievements of the national science are emphasized, paying special attention in the article to the reference literature on the history of Kazakh music. There are several stages in the development of this literature, each of which has contributed a lot of valuable things in recreating the appearance of the formation of the Kazakh musical art and preserving important historical facts. In conclusion, conclusions are drawn about the need for source studies that pose new challenges to the science of the XXI century and open up new horizons in the knowledge of the national spiritual heritage.